1995
DOI: 10.2307/3869991
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Plant Antenna Complexes Is Regulated by Post-Transcriptional Mechanisms in Tobacco

Abstract: Transgenic tobacco plants expressing antisense RNA directed against the multigene family of the light-harvesting complex of photosystem II (LHCII) were raised and analyzed biochemically and physiologically. A partial 5' terminal sequence with 509 nucleotides complementary to cab (chlorophyll a/b binding protein) genes reduced the amount of transcript to almost undectectable levels. We demonstrated for endogenous genes that a 5' terminal sequence with only 52 to 105 nucleotides complementary to the transit sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…Although the approach was successful, the frequency of substantial down-regulation in the transformed plants was low, and no plants lacking PSI-H were obtained in the T 1 generation. It has previously been reported that down-regulation of LHCII in an antisense approach was not observed, although the mRNA level was reduced to extremely low levels (28). On the other hand, down-regulation of the PSI-N subunit was very efficient in a similar cosuppression and antisense approach (14), and the successful down-regulation of the LHCI subunit Lhca4 by an antisense approach was recently reported (29).…”
Section: Discussionmentioning
confidence: 93%
“…Although the approach was successful, the frequency of substantial down-regulation in the transformed plants was low, and no plants lacking PSI-H were obtained in the T 1 generation. It has previously been reported that down-regulation of LHCII in an antisense approach was not observed, although the mRNA level was reduced to extremely low levels (28). On the other hand, down-regulation of the PSI-N subunit was very efficient in a similar cosuppression and antisense approach (14), and the successful down-regulation of the LHCI subunit Lhca4 by an antisense approach was recently reported (29).…”
Section: Discussionmentioning
confidence: 93%
“…The only previous attempt (to our knowledge) to effect Lhc gene expression by means of antisense inhibition was not successful. Flachmann and Kühlbrandt (1995) were not able to reduce the level of Lhcbl protein in tobacco (N. tabacuin L.), although the mRNA level was reduced to 5%. One reason for the difference between their results and ours could be that Lhcbl in a11 species investigated so far is encoded by a multigene family (Jansson et al, 1992), whereas Lkca4 is a single-copy gene, and the amount of Lkcbl transcript in Arabidopsis is approximately 20 times higher than that of Lkca4 (S. Jansson, unpublished data).…”
Section: Dlscusslonmentioning
confidence: 92%
“…This is different from the conclusions drawn from studies of antisense tobacco plants. Although there was a 95% reduction in Lhcb1 mRNA in tobacco plants containing antisense Lhcb1 constructs, the level of the Lhcb1 protein was not altered, suggesting that in tobacco, Lhcb1 protein levels are regulated primarily by post-transcriptional processes (Flachmann and Kühlbrandt, 1995). The variation in Lhcbm1 mRNA levels in complemented strains probably reflects position effects (differences in the site of integration of the exogenous DNA) on the rate of transcription.…”
Section: Physiological and Molecular Characterization Of Npq5mentioning
confidence: 93%